Regioselective assembly of fused pyrazole-azepine heterocycles: Synthesis of the 5-HT7 antagonist 1-benzyl-3-(4-chlorophenyl)-1, 4, 5, 6, 7, 8-hexahydropyrazolo[3, 4-d]azepine. (16th March 2021) - Dvorak, Curt A.; Liang, Jimmy; Mani, Neelakandha S.; Carruthers, Nicholas I.
Graphical abstract: Highlights: Selective pyrazole construction. Regioselective fused azepine-pyrazole assembly. Pyrazole triflate coupling. Selective Ring expansion. Selective 5-HT7 antagonist clinical candidate. Abstract: The synthesis of the 5-HT7 antagonist 1-benzyl-3-(4-chlorophenyl)-1, 4, 5, 6, 7, 8-hexahydropyrazolo[3, 4- d ]azepine is described using a regioselective assembly of a pyrazole ring fused to an azepine ring. Two different approaches were examined for the construction of the fused pyrazole-azepine heterocyclic core. These were based on the timing and method of installation of the appended aryl ring and construction of the fused heterocycle. The team focused on a route that featured a palladium coupling reaction to introduce the aryl ring via a pyrazole triflate and a selective alkylation to set the position of benzyl moiety on the pyrazole nitrogen. This led to a scalable synthesis of 1 (JNJ-18038683) allowing the discovery team to select and advance a clinical candidate.